STRATEGI KOMUNIKASI PEMASARAN COFFEE STREET KIRI6 MELALUI BAURAN PEMASARAN - Abdi Putra Pratama Adinata (JURNAL ILMIAH RESEARCH STUDENT, 2026)
With the high level of business competition in Indonesia, many business owners must consider the importance of marketing communication strategies in marketing their products and services. Coffe Street Kiri6 is a relatively young coffee shop in Sidoarjo, which must compete in a competitive market to attract consumers with different strategies and attractions than other coffee shops. Coffe Street Kiri6 takes the right strategy in its efforts to attract and increase the number of consumers. Therefore, Coffe Street Kiri6 has implemented several communication strategies in promoting and introducing its products to the public. The purpose of this study is to identify marketing communication strategies with the marketing mix at Coffe Street Kiri6, by looking at the following aspects: product mix, price, promotion, and place. This is to determine the strength of Coffe Street Kiri6 by using the 4P theory to attract consumer interest. This study uses a qualitative research type. Data in this study were obtained from observations, interviews, and documentation. The results obtained in this study are: the 4P marketing mix theory at the Coffe Street Kiri6 cafe has been well implemented. This shows that Coffe Street Kiri6 has a diverse and varied product/menu mix, not just a coffee menu. Coffe Street Kiri6 also develops product innovation by creating a seasoning menu every month. Pricing is also good based on market prices by setting prices that are not too high. Coffe Street Kiri6 itself is in a strategic location because it is in the city center, besides being close to schools, the facilities are also very adequate and comfortable. Promotions carried out by Coffe Street Kiri6 to attract consumers through social media such as Instagram, YouTube channel platforms, a number of sales promotions by establishing many collaborations with children's communities, cycling communities, and animal lover communities. Based on the overall results of the study, it is hoped that Coffe Street Kiri6 will continue to innovate, always maintaining the quality of the taste image that already has its own characteristics, also improving human resources (such as baristas, waiters/sales assistants) and maintaining promotions through social media so that it remains active and increasingly known to the public.